Implementation State Defense Values to Strengthen Border Community - Wahyudi, Wahyudi (The Republic of Indonesia Defense University, 2017)
This study aims to analyze the form in implementing the state defense values of the state defense in the border village of Sungai Limau in facing various challenges such as the susceptible threat of proxy war, using an analysis tool of the Bela Negara conception (State Defense) and Proxy War and Conception of Frontier Society. This study uses a qualitative method with case study approach by collecting data obtained from interviews, observation, and literature. The result shows that the implementation of the state defense values among the frontier communities in Sungai Limau has the potential to be developed into power in the form of attitudes and practices of national and state awareness and place Pancasila as the state ideology and means of unifying societies.